Lexical and Semantic Group of Nouns with the Hipersema ’National and Religious Affiliation’ in Serbian-Prizren Speech - Milosavljević, Tanja Z. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
Nationality as a universal category implies a description of the concept ethnos. The primary mode of verbalization of the category of ethnicity and the representation of the concept are the names of nations – ethnonyms. The merge of concepts of ethnos and religion in the domain of the social characterization of people by nomination according to given parameters was conditioned by the ethnic and religious structure of the population in Prizren in the first half of the 20th century (Serbs, Turks, Albanians, Cincari). The fragment of ethnicity is the component of a language image of the world of the dialect representative and it is based on the dichotomy own/foreign (свой – чужой). The primary ways of its representation are conceptualization, stereotypes and verbal association. The social category of national and religious affiliation and its semantic potential will be considered in terms of lexical-semantic group, in which the systematic and categorical component “representative of certain nation and religion” appears in the function of the invariant. The lexemes clustered around a hipersema formulated in this way have a nominal value, and depending on the dominant semantic mark “nation” and “religion” they form two lexical-semantic subgroups organized in a prototypical categorical opposition Serb/foreigner, orthodox/heterodox: lexical-semantic subgroup of nouns with the hipersema “a member of certain nation” and a lexical-semantic subgroup of nouns with the hipersema ”a member of certain religion”. The dialect material shows that in the speech of Serbs in Prizren the lexemes which are used to identify a person by nationality or religion are in certain systematic relations that are based on the principals of semantic derivational connections and they are also based on the relations of affiliation and opposites, which affects the structure of the lexical-semantic group. Antonyms are rarely seen in ethnic lexicon and they are represented by unitary antonyms of dichotomous division of concepts “own/foreign” which are conditioned by logical opposition that manifests in the language as the opposites Србин / туџ’ин (Ту́рч’ин, Арнау́тин, Лати́нин, Цига́нин, Го́га). The principle of the dichotomy was conducted in the category of naming according to religious affiliation (“orthodox/heterodox”), като́л’ик, лати́нин, мусл’и́ман, по́тур stand in opposition to рисја́нин forming an antonym paradigm. The stereotype notions of Serbs in Prizren about the nations they are closely connected to are expressed with an expressive nomination inventory (Ту́рч’е, Турч’ежи́ја, Белока́пац, Га́бел’, Габел’шти́ја, Габел’ч’и́́на, Ма́нга, Чифу́тка; поту́рко, потуре́шка).